Rural Healthcare IoT Architecture Based on Low-Energy LoRa - Dimitrievski, Ace; Filiposka, Sonja; Melero, Francisco José; Zdravevski, Eftim; Lameski, Petre; Pires, Ivan Miguel; Garcia, Nuno M; Lousado, José Paulo; Trajkovikj, Vladimir (MDPI AG, 2021)
Connected health is expected to introduce an improvement in providing healthcare and doctor-patient communication while at the same time reducing cost. Connected health would introduce an even more significant gap between healthcare quality for urban areas with physical proximity and better communication to providers and the portion of rural areas with numerous connectivity issues. We identify these challenges using user scenarios and propose LoRa based architecture for addressing these challenges. We focus on the energy management of battery-powered, affordable IoT devices for long-term operation, providing important information about the care receivers' well-being. Using an external ultra-low-power timer, we extended the battery life in the order of tens of times, compared to relying on low power modes of the microcontroller.